Stochastic Network Calculus - Jiang, Yuming; Liu, Yong (Springer Nature, 2009)
This book is devoted to a comprehensive treatment of this important field, a grand challenge for future networking research. It covers results from the authors as well as other researchers. Topics covered include Independent Case Analysis and its applications.